2012
DOI: 10.1111/j.1365-2427.2012.02749.x
|View full text |Cite
|
Sign up to set email alerts
|

Understorey environments influence functional diversity in tank‐bromeliad ecosystems

Abstract: Summary 1. A substantial fraction of the freshwater available in neotropical forests is impounded within the rosettes of bromeliads that form aquatic islands in a terrestrial matrix. The ecosystem functioning of bromeliads is known to be influenced by the composition of the contained community but it is not clear whether bromeliad food webs remain functionally similar against a background of variation in the understorey environment. 2. We considered a broad range of environmental conditions, including incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 39 publications
2
91
0
3
Order By: Relevance
“…According to Brouard et al (2012), mixotrophic Euglenophyceae are often found in partially or totally shaded bromeliads absorbing more organic than inorganic nitrogen. However, we suppose that sunlight has a greater influence on the diversity of Euglenophyceae (especially pigmented ones) more than the concentration of organic matter in bromeliad tanks.…”
Section: Discussionmentioning
confidence: 99%
“…According to Brouard et al (2012), mixotrophic Euglenophyceae are often found in partially or totally shaded bromeliads absorbing more organic than inorganic nitrogen. However, we suppose that sunlight has a greater influence on the diversity of Euglenophyceae (especially pigmented ones) more than the concentration of organic matter in bromeliad tanks.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, leaf litter and fine particulate organic matter (FPOM) constitute the main food resources (Brouard et al, 2012). Abiotic (leaching) and biotic processes (microorganisms and invertebrate detritivores) (Graça, 2001) successively decompose this material.…”
Section: Assessing the Role Of Canopy Cover On The Colonization Of Phmentioning
confidence: 99%
“…Abiotic (leaching) and biotic processes (microorganisms and invertebrate detritivores) (Graça, 2001) successively decompose this material. As in other aquatic ecosystems (Graça et al, 2015), the availability of organic detritus is a relevant factor to phytotelm communities (Walker et al, 1997;Brouard et al, 2012;Dézerald et al, 2013). Thus, both the quantity and quality of organic detritus can influence invertebrate abundance (Armbruster et al, 2002) and taxonomic richness (Kitching, 2000(Kitching, , 2001, as well as the biomass for functional feeding groups (Srivastava, 2006;Ptatscheck and Traunspurger, 2015).…”
Section: Assessing the Role Of Canopy Cover On The Colonization Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…Some invertebrates, such as oligochaetes and ostracods, spend their entire lives inside the cisterns of bromeliads (Montero et al 2010, Pinto & Jocqué 2013, while others are only found in such habitats in immature forms, mainly beetles and flies (Mestre et al 2001). These organisms play an important role (Sodré et al 2010), by helping to degrade the organic matter falling from the forest canopy, accelerating the release of nutrients to the bromeliad (Benzing 1990, Richardson 1999, Armbruster et al 2002, Araújo et al 2007, Brouard et al 2012. Furthermore, Martinelli et al (2008) mentioned the ecological importance of bromeliads due to their interaction with fauna, making a considerable contribution of the biodiversity of the communities in which they live.…”
Section: Introductionmentioning
confidence: 99%